Novel voltage stability index for electric power system monitoring - Oukennou, Aziz (Array, 2019)
This paper aims to develop a novel voltage stability index (NVSI) to evaluate and detect the voltage collapse proximity in the power system. This NVSI is based on the combination of two indices and the approximation made on the difference in angle between the sending bus and the receiving one in the power system. Compared to indices developed in the literature, the advantage of the new voltage stability index (NVSI) is that it can be computed very quickly and easily from power flow results, such as voltages, magnitudes and angles. The static and dynamic studies have been carried out on the IEEE 14-bus test system using PSAT Software. The proposed index has shown more sensitivity and simplicity, and that it can be used as a monitoring tool.